9x6+6x5−17x4−12x3+7x2+6x+1=0(x−1)(9x5+15x4−2x3−14x2−7x−1)=0x−1=0→x=19x5+15x4−2x3−14x2−7x−1=0(x−1)(9x4+24x3+22x2+8x+1)=0x1=x2=19x4+24x3+22x2+8x+1=0(x+1)(9x3+15x2+7x+1)=0x3=−19x3+15x2+7x+1=0(x+1)(9x2+6x+1)=0x3=x4=−19x2+6x+1=0⟺(3x+1)2=0→x5=x6=−31x1=x2=1;x3=x4=−1;x5=x6=−31
9x6+6x5−17x4−12x3+7x2+6x+1=0(x−1)(9x5+15x4−2x3−14x2−7x−1)=0x−1=0→x=19x5+15x4−2x3−14x2−7x−1=0(x−1)(9x4+24x3+22x2+8x+1)=0x1=x2=19x4+24x3+22x2+8x+1=0(x+1)(9x3+15x2+7x+1)=0x3=−19x3+15x2+7x+1=0(x+1)(9x2+6x+1)=0x3=x4=−19x2+6x+1=0⟺(3x+1)2=0→x5=x6=−31x1=x2=1;x3=x4=−1;x5=x6=−31